DisCoord: Co-creating DRR knowledge in Uganda through interaction in a serious game. (15th June 2021) - Delima, Gina; Jacobs, Liesbet; Loopmans, Maarten; Ekyaligonza, Mary; Kabaseke, Clovis; Kervyn, Matthieu; Mertens, Kewan
Abstract: Effective disaster risk reduction (DRR) presupposes awareness among key stakeholders on the causal factors that exacerbate disaster risks as well as a feeling of ownership over proposed DRR measures. Yet, the prevailing top-down communication of risk and the expert-centered knowledge have a limited impact in bringing significant positive change. Serious games respond to the need for a community-based DRR approach as they encourage a collective recognition of societal issues and co-learning at the different levels of the DRR governance system. However, there is still a gap in understanding how serious games facilitate co-creation of knowledge. In this article, we introduce DisCoord, a serious game first implemented in the landslide- and flood-prone Rwenzori mountains in South-West Uganda. Designed as a public pedagogy tool, Discoord bridges diverse views and sets of knowledge of DRR stakeholders separated by spatial and socio-cultural domains. Secondly, through a qualitative analysis of the dialogues, narratives and observation notes during the actual game sessions and debriefings, we explored the factors and processes that influence knowledge co-creation. Three different knowledge actors are involved in the co-creation process, namely the game designers, game facilitators and players. These actors have diverse pre-game views, which are expressed through the game rules, arguments, game strategies, and game outcomes, and are confronted within the public space provided by the game. We find that crises experienced during the game, real-life based arguments provided by the players and own interpretations by the players are key factors in the co-creation process. This study leads us to conclude that games like DisCoord are useful as a public pedagogy intervention as they bring different forms of knowledge together in a public space and facilitate co-learning. This paper also contends that countering a top-down approach of risk communication using a public pedagogy approach requires an openness towards the unpredictable, de-centered DRR, and plural co-learning outcomes.